Обеспечение заданной длины проводников в САПР TopoR - Lysenko, A. A.; Polubasov, O. B. (PE "Politekhperiodika", Book and Journal Publishers, 2009)
This article introduces mathematical models and algorithm for calculation of wire shapes of specified length, which are inscribed in an arbitrary trapezium. This helps to save workspace, which is especially important for any-angle routing. The presented algorithm allows maintaining the defined wire length with a maximum tolerance of 50 nm. For compatibility with CAD formats that do not support arc-shaped wires, TopoR creates approximated snake-like connections made up of straight lines only.